Bringing the era of nuclear weapons to an end: Speech given by Mr Jakob Kellenberger, President of the International Committee of the Red Cross, to the Geneva Diplomatic Corps on 20 April 2010. (7th April 2016) - Unknown
Abstract : In recent weeks and months, the issues of nuclear disarmament and nuclear non-proliferation have assumed a new urgency on the world stage. Energetic diplomatic efforts are heralding long overdue progress on nuclear weapons issues in the post-Cold War era.